Principle of patient's autonomy: problems of legal regulation in Ukraine - M. A. Anishchenko (Zaporozhye State Medical University, 2018)
The purpose of the research: to study the content of the principle of patient autonomy, the problem of its legal regulation in accordance with the legislation of Ukraine, outline the ways of their solution. Materials and methods: the regulatory and legal framework of Ukraine, the method of analysis, the method of synthesis, the comparative legal method. Results: The normative legal acts of Ukraine, in particular the Law of Ukraine "Fundamentals of Ukrainian legislation on health care", the Civil Code of Ukraine, enshrined the principle of patient autonomy. However, a number of norms are conflict-related, so they need legal improvement. Conclusions: The structure of the patient's autonomy principle includes the concept of informed consent and such basic rights of the patient as the right to choose a doctor, methods of treatment, and health facilities. At present, legislation that regulates the issue of consent of patients between 14 and 18 years of age, the refusal of medical intervention, the provision of complete information on the patient's health status, the right to choose a doctor and a health care institution, requires more precise changes, requires more precise regulation of the consent of the parents (or one from the parents) of the child to medical intervention.